2013
DOI: 10.1590/s1806-37132013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic and functional findings in severe COPD: comparison between the wood smoke-related and smoking-related disease

Abstract: OBJECTIVE: Wood smoke exposure is a risk factor for COPD. For a given degree of airway obstruction, the reduction in DLCO is smaller in individuals with wood smoke-related COPD than in those with smoking-related COPD, suggesting that there is less emphysema in the former. The objective of this study was to compare HRCT findings between women with wood smoke-related COPD and women with smoking-related COPD. METHODS: Twenty-two women with severe COPD (FEV1/FVC ratio < 70% and FEV1 < 50%) were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
3
33
0
4
Order By: Relevance
“…Confirmation of this from high-quality studies that include exposure measurements of HAP is continuing. The health risks associated with COPD, whether due to tobacco smoking or solid fuel exposure, do not differ much, although there seem to be more prominent airway disease manifestations and less emphysema with COPD associated with solid fuel smoke versus that associated with tobacco smoke exposure 161–163. Whether this difference is due to the magnitude of exposure, to differential smoke components, or to genetic background is unknown.…”
Section: Obstructive Lung Diseasementioning
confidence: 99%
“…Confirmation of this from high-quality studies that include exposure measurements of HAP is continuing. The health risks associated with COPD, whether due to tobacco smoking or solid fuel exposure, do not differ much, although there seem to be more prominent airway disease manifestations and less emphysema with COPD associated with solid fuel smoke versus that associated with tobacco smoke exposure 161–163. Whether this difference is due to the magnitude of exposure, to differential smoke components, or to genetic background is unknown.…”
Section: Obstructive Lung Diseasementioning
confidence: 99%
“…(41) Two recent studies comparing radiologic phenotypes between tobacco smoke-exposed and biomass smoke-exposed subjects matched for lung function found that the biomass group had more air trapping or peribronchial thickening and less emphysema than the tobacco group, suggesting an airway predominant phenotype. (42, 43) Another study of wood smoke-exposed women with COPD, the most common findings on HRCT scans were bronchial wall thickening, bronchiectasis, mosaic perfusion pattern, parenchymal bands, and tree-in-bud opacities. (44) These radiologic findings suggest a bronchitic clinical phenotype, as CB is associated with greater airway wall thickening and gas trapping on CT scan.…”
Section: Risk Factorsmentioning
confidence: 99%
“…I read with great interest the recent article by García et al ( 1 ) It should be noted that one rare, often overlooked and underrecognized, cause of respiratory tract infections and bronchial dilation is Mounier-Kuhn syndrome (MKS). The primary feature of MKS, also known as "tracheobronchopathia malacia", is congenital tracheal dilation accompanied by dilation of the main bronchi.…”
Section: To the Editormentioning
confidence: 99%
“…Li com grande interesse o recente artigo de García et al ( 1 ) Vale ressaltar que uma causa rara, muitas vezes negligenciada e sub-reconhecida, de infecções do trato respiratório e de dilatação brônquica é a síndrome de Mounier-Kuhn (SMK). A principal característica da SMK, também conhecida como "traqueobroncopatia malacia", é a dilatação traqueal congênita acompanhada de dilatação dos brônquios principais.…”
Section: Ao Editorunclassified
See 1 more Smart Citation